Urgency and emergency care for pregnant clients victims of abdominal trauma (Research, Society and Development, 2022)
Trauma is a bruise/injury that involves the exchange of energy between the environment and the body, it is also called "external causes" and the abdomen is a region vulnerable to trauma, which can compromise vital organs. The objective of this work is to analyze the scientific productions published from 1995 to 2021 related to the topic of abdominal trauma in pregnant women. Method: bibliographical review of a qualitative descriptive character. Results. Professionals who will care for this trauma victim must have knowledge about the pathophysiological elements that can occur in this situation in order to provide better care to the pregnant woman and reduce the high maternal-fetal morbidity and mortality. Conclusion: Many studies end up addressing trauma in general, however there is a scarcity of current national articles on the topic discussed, abdominal trauma in pregnant women, despite the limitations, this study proposes to encourage this search and provides insights so that future studies can incorporate tools for support mainly the nursing staff to provide better quality care to this patient.